The Impact of Corporate Social Responsibility Mediation on the Relationship between Earnings Management and Tax Avoidance - Kiryanto KIRYANTO; Luluk Muhimatul IFADA; Farikha AMILAHAQ (Communications of International Proceedings, 2021)
This study aims to determine the effect of earnings management on tax avoidance through corporate social responsibility. The population of this study was companies listed on the Indonesia Stock Exchange (IDX) in 2015-2019, while the sampling method in this study used a purposive sampling method which then obtained 71 samples of companies. The analytical technique used in this study is the SPSS version 20.0 program. The results of this study indicate that earnings management has no significant effect on CSR disclosure. However, earnings management has a significant positive impact on tax avoidance. Likewise, CSR disclosure has a significant negative effect on tax avoidance. The mediation results in this study imply that CSR disclosure cannot significantly mediate reducing the effect of earnings management on tax avoidance. This research has implications for policymakers about the importance of CSR to reduce tax avoidance. This research also brings theoretical implications, especially the relationship between CSR and tax avoidance.
Keywords: Earnings management; corporate social responsibility; tax avoidance.